Norepinephrine and acetylcholine changes during electrically-induced atrial fibrillation episodes in canine models - Zhang, X; Zhang, Y; Gao, F; Zhang, F; Yang, Z; Ouyang, S; Rao, M; Hou, Y (Cellular and Molecular Biology, 2016)
Atrial fibrillation (AF) is the most prevalent heart rhythm disorder, and autonomic nervous system (ANS) is important to AF. This study aims to identify whether changes in transmitters released by ANS could reflect their activities. The right atrium (RA) groups (1-40V) included RA500 and RA1000. While ANS groups received high-frequency electrical stimulation (1-8V, 20 Hz, 2 ms), including left stellate ganglion stimulation (LSGS) andleft cervical vagus trunk stimulation (LVTS). The induced rate of AF, duration and atrial effective refractory period (AERP) were measured. The blood was drawn for evaluation of norepinephrine (NE) and acetylcholine (Ach) concentrations. At 12-hours, RA tissue was dissected and compared against un-stimulated controls. While AF was induced by all groups, duration and AERP were significantly different between RA pacing groups and ANS-stimulated groups, respectively (P<0.05). Specific changes in profile of NE and Ach were associated with modality of stimulation. RA1000 tended to display most significant changes (P<0.05) compared to other groups while variables concentration levels were observed in other groups. In conclusion, electrically-induced AF initiated by various modalities of stimulation showed different changes in serum and RA tissues. Fast frequency pacing caused significant atrial electrical remodeling, including ANS activity change.